Law in the courts of love : literature and other minor jurisprudences - Goodrich, Peter, 1954- (Politics of language., 1996)
In the wake of current criticisms of the legal profession, Peter Goodrich presents us with a radical alternative vision of the law. He examines past legal systems offering up the possibility of a more humane system.